Selective Beta-Blockers on Chronic Obstructive Pulmonary Disease: A Literature Review - Van, An Thi Minh; Ahmad, Nawaid (Respiratory Science, 2024)
Chronic obstructive pulmonary disease (COPD) and cardiovascular disease (CVD) are usually coexisting. While beta-blockers are the indispensable management of an array of cardiovascular diseases, inhaled beta-receptor agonists are the central treatment for COPD patients. This review aims to assess the effect of beta-blockers on exacerbation rate, mortality, and quality of life among the COPD population. After the search on Cochrane Library, Pubmed, and Scopus, 15 relevant full-text articles published between 2012 and 2022 were included. We compared selective beta-blockers versus either non-users or non-selective agents. The results showed that selective beta-blockers did not increase the mortality and exacerbation rate in the COPD population and evidence on health-related quality of life is still sparse. However, more RCTs should be carried out for more precise information.